Benchmarking institutional and structural indicators in EU candidate and potential candidate countries - Roberto Alvarez Orviz; Li Savelin (European Central Bank (ECB), 2017)
This paper reviews institutional and structural challenges in countries preparing for EU membership, i.e. Albania, Bosnia and Herzegovina, Kosovo*, the former Yugoslav Republic of Macedonia, Montenegro, Serbia and Turkey. Sound institutions and solid economic structures are not only the cornerstones of EU accession (as defined by the Copenhagen political and economic criteria), but are also crucial for achieving higher income levels and sustainable long-term growth. This paper finds that the EU candidate and potential candidate countries (EU CC/PCC) fare worse than the majority of EU Member States in a number of institutional and structural metrics, such as business environment, access to finance, judicial system, trade and competitiveness, labour market and education and institutional governance. When comparing EU CC/PCC among themselves, large intra-group disparities emerge. Countries such as the former Yugoslav Republic of Macedonia, Montenegro and, to a certain extent, Serbia and Turkey, tend to score on average higher than Albania, Bosnia and Herzegovina and Kosovo. While many EU CC/PCC have improved the quality of their institutions and economic governance over the past decade, it is crucial that they preserve the reform momentum to enable a sustainable convergence with the EU.
Keywords: F13; F15; G21; O11; O43; 330; institutions; economic growth; EU accession; Western Balkans; businessenvironment; access to finance; trade integration; governance